STRATEGI PEMASARAN HASIL PERIKANAN DI NEGERI HUKURILA KECAMATAN LEITIMUR SELATAN KOTA AMBON - Wattimury, Margie; Bawole, Dionisius; Apituley, Yolanda M. T.; Pattimukay, Kesya; Snall, Dealistra (HIRONO : Jurnal Pengabdian Masyarakat, 2026)
The extension activities carried out in Hukurila Village, South Leitimur Sub-district, Ambon City, aimed to improve fishermen’s knowledge and skills regarding marketing strategies for fishery products in Hukurila Village, in order to resolve the marketing issues faced by the fishermen’s group. The methods employed included extension sessions, focus group discussions (FGDs) and evaluations to ensure the programme’s sustainability. The results of the evaluation of the outreach activities indicate that this Community Service (PkM) initiative has successfully enhanced fishermen’s knowledge and capabilities in marketing fishery products. Furthermore, the results of the FGDs indicate that marketing development efforts through the diversification of processed products, the utilisation of digital technology, and collaboration with the government and relevant institutions will present significant opportunities for strengthening fishermen’s capacity and improving supporting facilities. This will enable more efficient marketing of fishery products, enhance competitiveness, and expand markets, thereby supporting the welfare of the community in Hukurila